Variety of Characteristic Magnetic Material on Permanent Magnet Synchronous Generator (PMSG) - Syamsyarief Baqaruzi; Amrina Mustaqim; Putty Yunesti; Gde KM Atmajaya; Ali Muhtar; Sabhan Kanata (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2022)
Wind energy conversion system, one of the main components is a Permanent Magnet Synchronous Generator (PMSG). During the past two decades, many types of per- manent magnet generators for wind power applications have been the research topic. This study focuses primarily on designing a PMSG to create, simulate, and analyze an internal permanent magnet topology with twelve plots and eight poles. We limit with the simulation was carried out at a rotational speed of 1000rpm, and a type of permanent magnet material, Ceramic 11, SmCo 26/26, and NdFeB 48/11. The result of the analysis is that permanent magnets applied in the design of a generator impact its output power and efficiency. At 15 Ω and 60 Ω loads, SmCo 26/26 and NdFeB 48/11 are the only ones that fulfill the specified requirements in this investigation. The permanent magnet type with the most optimal characteristics is Neodymium Iron Boron 48/11 because it has a high flux density, thus causing the electrical energy generated to be greater than other types of permanent magnets. The 48/11 NdFeB permanent magnet generates the most output power, 2110.86 W when loaded with 15 Ω. The best efficiency of 89.38 percent for the PMSG 12 slot eight poles occurs when the load is 15 on the 48/11 NdFeB permanent magnet.